Spin photonics: from transverse spin to photonic skyrmions - Shi, Peng; Du, Luping; Yuan, Xiaocong (Nanophotonics (Berlin, Germany), 2021)
Spin angular momentum associated with circular polarization is a fundamental and important aspect of photons both in classical and quantum optics. The interaction of this optical spin with matter and structures results in many intriguing optical effects and state-of-the-art applications covered under the emerging subject of spin optics. Distinct from longitudinal optical spin along the mean wavevector, transverse spin, the corresponding vector of which is perpendicular to the mean wavevector, prevails and plays a significant role in confined electromagnetic waves such as focused beams, guided waves, and evanescent waves. In the optical near-field, these transverse spins are generated owing to the spatial variation of the kinetic momentum of confined electromagnetic waves, where the spin and orbital angular momenta are strongly coupled, leading to many interesting topological spin structures and properties. Several reviews on optical transverse spins have been published in recent years in which their concepts and the various configurations producing them were introduced systematically. Here, we introduce in this review the underlying physics and dynamics of transverse spin and the resultant topological structures and properties such as the photonic skyrmions and merons. We term this sub-area ‘spin photonics’, its scope being to cover the design and research of spin structures in strongly confined electromagnetic fields with unique properties and applications. The concepts and framework reviewed have importance in optics, topological photonics, metrology, and quantum technologies and may be used to extend spin-dynamics concepts to fluidic, acoustic, and gravitational waves.